OxLDL plasma levels in patients with Alzheimer's disease - Marina Felipe Grossi; Maria das Graças Carvalho; Josianne Nicácio Silveira; Gisele Santos Gonçalves; Karina Braga Gomes; Maria Aparecida Bicalho; Ieda de Fátima Oliveira Silva (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: The objective of this study was to characterize the conventional lipid profile, oxLDL levels and ApoE polymorphism in patients with Alzheimer's disease (AD) and in elderly individuals without cognitive impairment. Methods: Eighty elderly individuals were selected and the levels of oxLDL were determined using the ELISA kit, and ApoE gene polymorphism was investigated using polymerase chain reaction-restriction fragment length polymorphism. Results: Significantly reduced levels of oxLDL were observed in patients with AD compared to the control group. A higher frequency of the ApoE ε4 allele was observed in patients with AD compared to controls. No difference was observed for total cholesterol, HDL-C, and LDL-C levels between the two groups, while triglyceride levels were higher in controls compared with patients with AD. Conclusion: The data analyzed together did not reveal significant differences in lipid profiles, including oxLDL levels. However, the importance of lipid changes in the genesis of the disease cannot be ruled out. Nevertheless, the ApoE ε4 allele was significantly more frequent in patients with Alzheimer's dementia in agreement with previous findings in the literature, but this genetic component did not change the levels of oxLDL.